KOLEKSI KLIPING SURAT KABAR DI PERPUSTAKAAN CENTRE FOR STRATEGIC INTERNATIONAL STUDIES (CSIS) SEBUAH KAJIAN - Damaji Ratmono (Perpustakaan Nasional RI, 2019)
Daily and weekly newspapers published in Indonesia often present interesting news and articles that can add insight to their reader. Often, these interesting news or articles are only needed in a single day. It would be positive if these news or articles are collected and clipped per topic so thet its information can be easily obtained when needed. This clipping activity is carried out by CSIS (Centre of Stategic and International Studies). Based on observations and interviews with CSIS, it is know that this national and international scale institution, which is located on Jalan Tanah Abang, Central Jakarta, has been clipping newspapers from 1971 to present (47 years-now) and has collected at least 10.000 scrapbook titles. Based on observation and interviews, it is also known that the method used to perform clipping at CSIS is ordnere method. In addition, the clippings that have been compiled were indexed in a separate book to facilitate reader to search fro topics they want. The existence of a clipping collection at CSIS can be very important for researchers to support research activities at CSIS as well as for publics.